PENGEMBANGAN MULTIMEDIA PEMBELAJARAN MATERI WUJUD BENDA BERBASIS WORDWALL DI KELAS IV SD NEGERI 55/I SRIDADI - Zahara, Fatimah; Faizal Chan; Issaura Sherly Pamela (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This development research aims to (1) describe the procedure for developing Multimedia learning of object form material based on wordwall in class IV SDN 55/I Sridadi, (2) to determine the level of validity of the development of multimedia learning of object form material based on wordwall in class IV SDN 55/I Sridadi, (3) to determine the level of practicality of the product from the development of Multimedia learning of object form material based on wordwall in class IV SDN 55/I Sridadi. The method used in this study is Research and Development (R & D) using the Lee & Owens (2004) development model which has five stages, namely (Analyze, Design, Development, Implementation, Evaluation). The type of research data is in the form of qualitative data and quantitative data. The source of research data was obtained from validators, teachers, and students. Quantitative data were obtained from the results of the material validation questionnaire, media validation, and language validation, practical questionnaires and student response questionnaires. This research was conducted in class IV SDN 55/I Sridadi. The development procedure produced a Multimedia product based on wordwall material about the form of objects. The results of the media product validation test from material experts reached a percentage of 94% with a very valid category, secondly the results of the media expert validation reached a percentage of 74.28% with a fairly valid category, thirdly the results of the language expert validation reached 90% with a very valid category. The practicality of learning multimedia reached a percentage of 97.5% with a very practical category. For the practicality of the student response questionnaire acquisition of 97.16%, with the criteria of very practical practicality. Based on the results of this study, it can be concluded that wordwall-based learning Multimedia is considered valid and practical to be used as a supporting media for learning science on the material of the form of objects in class IV SDN 55/I Sridadi.